(untitled) (The Shivapuri Journal, 2025)
Ethnic diversity, if managed well, can be an asset for a nation, enhancing cultural richness, fostering social cohesion, and strengthening national resilience. However, when ethnic issues are ill-treated, they can lead to fragmentation, violent conflicts and long-term instability. This article explores the relationship between ethnic diversity and national security, drawing comparisons from the Balkans, the United States, Europe and South Asian nations, with a particular focus on Nepal. The paper delves into historical and contemporary cases where ethnic tensions have either strengthened or undermined security, examining the crucial factors that determine the path of ethnic issues within nations. It will analyze how political leaders’ handling of ethnic relations plays a pivotal role in either fostering national unity or exacerbating divisions. In the context of Nepal, characterized by its diverse geography and over 142 ethnic groups, the article argues that carefully managing ethnic diversity can serve as a stabilizing factor in national security. It emphasizes the importance of inclusive governance, effective communication and inter-ethnic dialogue to ensure that ethnic tensions do not evolve into full-blown conflicts, as has been the case in many other parts of the world. The article concludes that while ethnic diversity poses challenges, it offers significant opportunities for national strength if managed with care and foresight.